(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Todayinternet has become an ongoing emerging source that tends to expand more andmore. So businesses are spending more on online advertisement than before.Online advertising, also called online marketing or Internet advertising is aform of marketing and advertising which uses the Internet to deliver messages to consumers. It includes emailmarketing, mobile advertising and display advertising etc. The growth of thisparticular media attracts the attention of advertisers as a more productivesource to bring in consumers. The main aim of this research paper is to findout the reasons of growth of online advertisement, making effective onlineadvertisement, to study the factors affecting online advertising, knowledgeabout online advertising spending in India in March 2015, consumer facts andfigures towards online advertising and list of 10 ad agencies in India.